Trowbridge Road - Pixley, Marcella Fleischman (Candlewick Press, 2020)
The idyllic suburban street known as Trowbridge Road has served as a sanctuary for June Bug away from the silence and secrets of her home--silence and secrets brought about by her mother, who is still obsessed with how June's father died of AIDS. One day, a strange boy named Ziggy moves on to Trowbridge Road, and June and he become friends almost immediately, sharing their imaginations and troubles, and finding new ways to rescue each other from the demons of their lives.